1994
DOI: 10.1111/j.1432-1033.1994.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

The Heterodisulfide Reductase from Methanobacterium Thermoautotrophicum Contains Sequence Motifs Characteristic of pyridine‐Nucleotide‐Dependent Thioredoxin Reductases

Abstract: The genes hdrA, hdrB and hdrC, encoding the three subunits of the iron-sulfur flavoprotein heterodisulfide reductase, have been cloned and sequenced. HdrA (72.19 kDa) was found to contain a region of amino acid sequence highly similar to the FAD-binding domain of pyridine-nucleotidedependent disulfide oxidoreductases. Additionally, 11 0 amino acids C-terminal to the FAD-binding consensus, a short polypeptide stretch (VX,CATID) was detected which shows similarity to the region of thioredoxine reductase that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
58
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 47 publications
(43 reference statements)
2
58
0
Order By: Relevance
“…marburgensis HdrCB, which are conserved in both enzymes [3,5]. A detailed spectroscopic characterization showed that the active site harbours a [4Fe)4S] cluster [7,8] …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…marburgensis HdrCB, which are conserved in both enzymes [3,5]. A detailed spectroscopic characterization showed that the active site harbours a [4Fe)4S] cluster [7,8] …”
mentioning
confidence: 99%
“…This disulfide is generated in the final step of methanogenesis [1]. Two types of Hdr have been identified and characterized from distantly related methanogens [2][3][4][5][6].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…HdrB contains no sequence motif characteristic for the binding of known cofactors but has two unique cysteine-rich sequence motifs (CX [31][32][33][34][35][36][37][38][39] CCX [35][36] CXXC) of unknown function, designated as the CCG domain in the Pfam protein families database (accession number PF02754) (8). The ferredoxin-like subunit HdrC contains two canonical binding motifs for [4Fe-4S] clusters (9). HDR from Methanosarcina species lacks a homologue of the M. marburgensis HdrA subunit, whereas subunits HdrC and HdrB are conserved in the putative fusion protein HdrD ( Figure 1).…”
mentioning
confidence: 99%